Physical activity, health and well-being among a nationally representative population-based sample of middle-aged and older adults in India, 2017–2018 - Supa Pengpid (2022)
Background: This study aimed to determine the association between physical activity (PA) and health and well-being in middle-aged and older community-dwelling adults in India. Methods: The cross-sectional sample consisted of 72,262 individuals (≥45 years) from the Longitudinal Ageing Study in India (LASI) Wave 1 in 2017–2018. Logistic regression, adjusted for relevant confounders, was used to predict associations between PA levels and 23 health indicators. Results: In all 23.8% of participants were inactive, 12.9% had low, 7.6% moderate, and 55.7% high PA. In the final adjusted logistic regression analyses, higher PA levels were associated with better mental health (less insomnia symptoms, less depressive symptoms, less loneliness, and better cognitive functioning), and better well-being (self-rated health status, life satisfaction, happiness, functional ability, and hand grip strength). Moreover, moderate and/or high PA were negatively associated with diabetes, heart disease, stroke, hypertension, chronic lung disease, vision impairment, cataract, chronic renal failure, and Alzheimer's disease/dementia. While in unadjusted analysis, moderate and/or high PA were protective against major depressive disorder and bone or joint diseases, this became non-significant in the adjusted model. PA was not significantly associated with abdominal obesity and cancer. Conclusion: Overall, higher PA levels were positively associated with 10 of 11 mental health and well-being indicators as well as being protective against 9 of 12 chronic conditions.